Electric and Magnetic Properties of Hydrogels Doped with Cu Ions - Coskun, R.; Okutan, M.; Yalcin, O.; Kosemen, A. (POLISH ACAD SCIENCES INST PHYSICS, 2012)
The electric and magnetic properties of Cu doped and pure/undoped hydrogels were investigated by impedance spectroscopy and electron spin resonance techniques, respectively. The capacitance and dissipation factor (tan delta) were measured in the frequency range of 100 Hz-10 MHz at room temperature. The Cole-Cole plots for the Cu doped dry and pure dry hydrogels have been used to describe the characteristic change of electrical properties in mentioned temperature interval. The comparison between Cu ions doped and pure/undoped samples is done using the impedance spectroscopy and the electron spin resonance techniques. Electron spin resonance signal for pure, Cu doped wet and Cu doped dry samples are not any power absorption signal, near the symmetric with respect to the resonance field values according to the dry sample and asymmetric for resonance field/base line, respectively.
Keywords: DRUG-DELIVERY; DIELECTRIC-RELAXATION; POLYMER; CHELATE; Physics